Preliminary Investigations of Polylactic Acid (PLA) Properties - Subramaniam, Shathiswara Rao; Mahendran, Samykano; Selvamani, Sathish Kumar; W. K., Ngui; K., Kadirgama; Sudhakar, K.; M. S., Idris (AIP Publishing, 2019)
Additive manufacturing is a technology capable to directly manufacture 3D physical model alongside with their inserted mathematical model in an additive nature, where the materials are fused together to form a product, unlike the traditional manufacturing method. The emergence of 3D printing has secured a shorter cycle time for designing and developing innovative products. One of the most commonly used additive manufacturing technology is Fused deposition modelling (FDM). 3D printing applications has seen an immense growth, where it has included more load bearing parts targeted to fit an intended application as per user’s requirement. Certain level of mechanical property information is being demanded as a benchmark to assess the strength of printed part in whole. This research work aims to investigate the tensile properties of PLA and find the optimum printing parameter combination using low-cost fused filament printer. Two parameters chosen to be varied in this research are raster angle and infill density, with value of 20°, 40°, 60° and 20%, 50%, 80% respectively. Tensile specimens with combination of these two parameters were printed according to ASTM D638 type 1 standard, with having layer height of 0.1mm as a constant. Tensile tests were conducted on the 3D printed PLA specimens to determine the best suited parameter combination that will result in optimum mechanical properties. Three mechanical properties were analysed, namely ultimate tensile strength, elastic modulus and yield strength. From the 9 combinations of parameter, the optimum combination was determined, which are 0.1 mm layer height, 40° raster angle, and 80% infill density of 3rd combination. Its optimum mechanical property is 32.93754MPa for ultimate tensile strength, 807.48931 MPa for elastic modulus and 26.08234 MPa for yield strength.